REQUIREMENTS FOR DETECTION OF ENVIRONMENTAL CRIME - Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Detection and identification of ecological crimes requires specific, specialized knowledge of the competent authorities and the work of the police in detecting and proving involves cooperation with the competent inspection services and other organs. Of particular significance in detecting offenses of ecological criminal is timely and properly taking fisrt operation, in particular crime scene investigation and situational and reconstructive expertise. In order to find answers to the gold forensics issues when conducting investigation, and to identify, fix and secure traces and objects of the offense, it is necessary to engage experts in the appropriate field. In order found traces and objects to may be used in the criminal proceedings, they need to be processed in accordance with all the rules of criminalistics. Therefore, timely consultation between the police, the public prosecutor and the forensics are essential for the successful investigation and prosecution. Keywords: Environmental crime, detection, proving, crime scene investigation